Correction to: Emotional Contagion in Collaborative Virtual Reality Learning Experiences: An eSports Approach (Education and Information Technologies, (2023), 28, 11, (15317-15363), 10.1007/s10639-023-11769-7) - Dirin, Amir; Nieminen, Marko; Laine, Teemu H.; Nieminen, Lassi; Ghalebani, Leila (Education and Information Technologies, 2024)
The author name “Ghalebani” was misspelled as “Ghalabani” in the original publication of this article. The original article has been corrected.